Gerakan Pelestarian Cagar Alam berbasis Masyarakat untuk Meningkatkan Income Masyarakat Desa Sawahluhur Kota Serang - Puspita Maelani; Agustiawan Agustiawan; Euis Suhartini (Gapenas Publisher, 2022)
This service is carried out because of the potential for nature reserves owned by the village of sublime rice fields. However, the condition of public awareness is still less concerned in preserving nature. So the purpose of this service is to socialize the movement for preserving the island's two nature reserves, and increasing people's income. The method is carried out through 4 stages, namely the preparation, implementation, implementation and evaluation stages. The result of this service is the participation of the community in preserving the nature reserve, awareness of protecting the environment and taking advantage of business opportunities such as the development of a local creative economy that is owned, from the existence of tourism business products